THU301 Natural History Of Pregnancy And Pregnancy Outcomes In Subjects With Lipodystrophy - Neal, Trinity J; Startzell, Megan S; Cochran, Elaine; Lightbourne, Marissa; Brown, Rebecca J (Journal of the Endocrine Society, 2023)
Disclosure: T.J. Neal: None. M.S. Startzell: None. E. Cochran: None. M. Lightbourne: None. R.J. Brown: None. Lipodystrophy syndromes are a group of rare heterogenous disorders characterized by deficiency of adipose tissue in a regional distribution (Partial Lipodystrophy, PL) or all of the body (Generalized Lipodystrophy, GL), leading to severe insulin resistance, diabetes, hypertriglyceridemia, non-alcoholic steatohepatitis, and polycystic ovarian syndrome. During pregnancy in patients with lipodystrophy, insulin resistance worsens during late gestation, leading to pregnancy complications that may threaten the lives of the fetus and mother. Case reports have suggested increased risk of pregnancy complications such as pre-eclampsia in patients with lipodystrophy. We sought to systematically examine pregnancy complications and offspring outcomes in lipodystrophy through a prospective study involving structured interviews with patients with known lipodystrophy and past pregnancy. Data were collected in 7 patients with PL (2 LMNA, PPARG, 4 unknown genetic cause) and 1 with GL (AGPAT2). These 7 patients had 21 pregnancies (mean 2.6), including 19 singleton and 2 twin gestations. 14 pregnancies (67%) were spontaneous and 7 (33%) required fertility treatment. 10 pregnancies (48%) in 6 patients resulted in 12 live births (7 term, 3 preterm; 3 vaginal and 8 C-section delivery) and 11 (52%) resulted in miscarriage (9 first trimester, 2 second trimester in 1 patient due to cervical insufficiency). There were no episodes of acute pancreatitis during pregnancy. Among the 10 pregnancies resulting in live birth, 100% were complicated by diabetes. 5 (50%) had pre-gestational diabetes and 5 (50%) had gestational diabetes that resolved after delivery. 8 (80%) required insulin during pregnancy (of whom none required insulin pre-pregnancy). 5 (50%) of these pregnancies were complicated by pre-eclampsia. Among all 21 pregnancies, metformin was used in 8 (38%), insulin in 8 (38%), metreleptin in 4 (19%) pregnancies (all 4 of which were in 1 patient with GL), and fenofibrate in 2 (9.5%). Among 12 offspring, 1 (8%) was small for gestational age (GA), 8 (67%) were appropriate for GA and 3 (25%) were large for GA. 6 (50%) had neonatal hypoglycemia. In summary, pregnancies in women with lipodystrophy showed high complication rates, including very high rates of miscarriage, diabetes, and pre-eclampsia. Larger studies are needed to determine how management of these patients during pregnancy, including with newer treatments such as metreleptin for GL, affects pregnancy and offspring outcomes. Presentation: Thursday, June 15, 2023